Properties of nickel-supported palm oil fuel ash (Ni-POFA) catalyst produced via in situ glycine-nitrate combustion for methane cracking - Nurul Husna Elyana, Hanifa (2021)
Methane cracking is an alternative route for H2 production with zero COx emission and low GHGs emissions. Palm oil fuel ash (POFA) is an agricultural waste and has a potential to be developed as a catalyst support for methane cracking due its high silica (SiO2) content. In this study, factors which influence catalyst properties have been explored, aiming for Ni-POFA catalyst with excellent performance and stability. Initially, properties of POFA as catalyst support has been evaluated in POFA pre-treatment where the effects of various solvents (HCl, citric acid, and NaOH) and pre-treatment techniques (conventional stirring and ultra-sonication) have been investigated. A new preparation method for Ni-POFA; in situ glycine-nitrate combustion process (in situ GNP) also has been explored. Finally, effects of Ni loading (5–20 wt.%) and gas hourly space velocity (GHSV) (5,000–25,000 mL/h.g) have been investigated. Catalytic performance of Ni-POFA catalyst was evaluated for methane cracking at 550°C for 6 hrs. The POFA and Ni-POFA catalyst were characterized using XRF, XRD, BET surface area, H2-TPR, H2 pulse chemisorption, FESEM and TGA. From the results, SiO2 content in the POFA has been improved from 42 to 72% with citric acid pre-treatment. Ni-POFA catalyst produced with POFA treated using ultra-sonication technique had a larger BET surface area (12.2 m2/g) compared to one with POFA treated using conventional stirring technique (9.2 m2/g). Both citric acid solution and ultra-sonication technique were found to be the best solvent and technique for POFA pre-treatment giving the Ni-POFA a reasonable catalytic performance in methane cracking (66% of initial CH4 conversion and 4.2% of initial H2 yield). Meanwhile in the catalyst preparation study, Ni-POFA catalyst prepared using in situ GNP method (Ni-POFA (GNP)) has exhibited a good catalytic performance with an initial CH4 conversion of 60% and 8.7% of initial H2 yield. This is attributed to strong interaction between Ni and POFA, and high Ni metal dispersion in Ni-POFA (GNP) as evidenced by H2-TPR and H2-chemisorption analysis. Nevertheless, a higher degradation rate of CH4 conversion was observed in Ni-POFA (GNP) compared to one produced using impregnation (Ni-POFA (Imp)). It is suggested that Ni-POFA catalyst synthesized using in situ GNP was not only active for H2 production but also for carbon formation. Type of carbon formed was also varied upon the catalyst preparation method when filamentous-types of carbon was found deposited on the Ni-POFA (GNP) while the Ni-POFA (Imp) was covered by the encapsulating carbon. For the effect of Ni loading, 15 wt.% was found to be the optimal Ni loading for Ni-POFA catalyst. Additionally, the Ni loading significantly influenced the dimension of filamentous carbons available on the Ni-POFA surface. Finally, Ni-POFA gave the highest catalytic performance with 87% initial CH4 conversion and 27% initial H2 yield using 7,000 mL/g.h GHSV. As a conclusion, POFA exhibits a good potential as a catalyst support for Ni. POFA pre-treatment and in situ GNP preparation have successfully improved the catalyst properties, thus enhanced the catalytic performance of Ni-POFA catalyst in methane cracking for hydrogen production.